Data Sharing in the Undiagnosed Diseases Network. Issue 10 (27th August 2015) - Brownstein, Catherine A.; Holm, Ingrid A.; Ramoni, Rachel; Goldstein, David B.; Members of the Undiagnosed Diseases Network
ABSTRACT The Undiagnosed Diseases Network (UDN) builds on the successes of the Undiagnosed Diseases Program at the National Institutes of Health (NIH UDP). Through support from the NIH Common Fund, a coordinating center, six additional clinical sites, and two sequencing cores comprise the UDN. The objectives of the UDN are to: (1) improve the level of diagnosis and care for patients with undiagnosed diseases through the development of common protocols designed by an enlarged community of investigators across the network; (2) facilitate research into the etiology of undiagnosed diseases, by collecting and sharing standardized, high‐quality clinical and laboratory data including genotyping, phenotyping, and environmental exposure data; and (3) create an integrated and collaborative research community across multiple clinical sites, and among laboratory and clinical investigators, to investigate the pathophysiology of these rare diseases and to identify options for patient management. Broad‐based data sharing is at the core of achieving these objectives, and the UDN is establishing the policies and governance structure to support broad data sharing.